An integer factorization algorithm using elliptic curves - Salehyan, Parham (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2023)
The theory of elliptic curves involves a nice mix of algebra, geometry, analysis and number theory. The main objective of this text is to present a introduction to this theory in an accessible manner to undergraduate students and apply it to one of the most familiar problems about integers: their factorization into prime numbers.